Analisis Dampak Pandemi Corona Virus Terhadap Tingkat Kesadaran Masyarakat dalam Penerapan Protokol Kesehatan - Pinasti, Faura Dea Ayu (Wellness And Healthy Magazine, 2020)
Coronavirus is a new type of virus that is now shocking the world because it has infected thousands of millions of global people in a short time. Anticipating the spread and increase in the number of patients, the application of health protocols needs to be done by the community. Some health protocols during the Corona pandemic period are; wearing masks, applying social distancing or physical distancing, maintaining hand hygiene and applying the ethics of coughing and sneezing. So this study aims to determine the level of public awareness in the application of health protocols during the Coronavirus pandemic. This study uses a cross-sectional method and an observational study. While the data collection process was carried out through a google survey and WhatsApp with a total sample of 130 participants. Based on the data obtained, most people have implemented several health protocols such as; wearing masks, applying social distancing or physical distancing and applying the ethics of coughing and sneezing well. But the implementation of health protocols such as maintaining hand hygiene has not been done well. 52.3 percent and 56.9 percent of participants did not wash their hands before eating and did not bring hand sanitizers when traveling as a form of self-protection.